Bio-inspired metaheuristics applied to the parametrization of PI, PSS, and UPFC–POD controllers for small-signal stability improvement in power systems - Fortes, Elenilson V.; Martins, Luís Fabiano Barone; Miotto, Ednei Luiz; Araujo, Percival Bueno [UNESP]; Macedo, Leonardo H. [UNESP]; Romero, Rubén [UNESP] (Springer, 2022)
The firefly algorithm (FA) and the artificial bee colony (ABC) algorithm are used in this study to perform a coordinated parametrization of the proportional-integral and supplementary damping controllers, i.e., power system stabilizers (PSSs) and the unified power flow controller (UPFC)–power oscillation damping set. The parametrization obtained for the controllers should allow them to damp the low-frequency oscillatory modes in the power system for different loading scenarios. The power system dynamics is represented using a model based on current injections, known as the current sensitivity model, which implies that a formulation by current injections for the UPFC should be formulated. To validate the proposed optimization techniques and the current injection model for the UPFC for small-signal stability, simulations are carried out under two distinct perspectives, namely, static and dynamic analysis, using the New England system. The results demonstrated the effectiveness of the UPFC’s current injection model. Moreover, it was possible to verify that the FA performed better than the ABC algorithm to solve the discussed problem, accrediting both the UPFC current injection model and the FA algorithm as new tools for small-signal stability analysis in electrical power systems.
Keywords: Artificial bee colony; Current sensitivity model; Firefly algorithm; POD; PSS; UPFC